A bibliometric study on the R&D funding and academic research performance in Shenzhen. (5th February 2022) - Zou, Yawen
Abstract: This study aims to shed light on how research and development (R&D) funding plays a role in producing academic articles in Shenzhen from 2008 to 2020. The metadata from the Web of Science database, various governmental documents, and relevant literature can help understand the structure of R&D spending, the publication of scholarly articles, the funding programs, recipient institutions, research categories, and how geographical factors play a role. The prosperous economy has enabled the increased input of municipal and national governmental funding. The majority of scholarly articles are now funded publicly rather than privately and are published by public universities and research institutes rather than private firms. Geography plays an important role in the cooperation of Shenzhen's scientists and other domestic and worldwide scholars. To better understand the academic performance of Shenzhen, this article used a bibliometric method to compare its academic performance with that of Silicon Valley.